Amino Acid-Based Metabolic Profile Provides Functional Assessment and Prognostic Value for Heart Failure Outpatients. (19th May 2019) - Wang, Chao-Hung; Cheng, Mei-Ling; Liu, Min-Hui; Fu, Tieh-Cheng
Abstract : Functional capacity is a crucial parameter correlated with outcomes. The currently used New York Heart Association functional classification (NYHA Fc) system has substantial limitations, leading to inaccurate classification. This study investigated whether amino acid-based assessment on metabolic status provides an objective way to assess functional capacity and prognosis in heart failure (HF) outpatients. Plasma concentrations of histidine, ornithine, and phenylalanine (HOP) were measured on 890 HF outpatients to assess metabolic status by calculating the HOP score. Cardiopulmonary exercise testing (CPET) was performed in 387 patients to measure metabolic equivalents (MET) in order to define the functional class based on MET (MET Fc). Patients were followed for composite events (death/HF-related rehospitalization) up to one year. We found only 47% concordance between the MET Fc and NYHA Fc. HOP scores worked better than NYHA Fc for discriminating patients with MET Fc II and III from those with MET Fc I, with the optimal cutoff value set at 8.8.HOP   scores ≥ 8.8 were associated with risk factors for composite events in different kinds of HF populations and were a powerful predictor of composite events in univariate analysis. In multivariable analysis, HOP   scores ≥ 8.8 remained a powerful event predictor, independent of other risk factors. Kaplan-Meier curves revealed that HOP scores of ≥8.8 stratified patients at higher risk of composite events in a variety of HF populations. In conclusion, amino acid-based assessment of metabolic status correlates with functional capacity in HF outpatients and provides prognostic value for a variety of HF populations.